Kinetic analysis of N-acylphosphatidylserine accumulation and implications for membrane assembly in Rhodopseudomonas sphaeroides. - Cain, B D (1982)
The accumulation of N-acylphosphatidylserine (NAPS) in response to the inclusion of Tris in the growth medium of Rhodopseudomonas sphaeroides strain M29-5 has been examined. In the accompanying paper (Donohue et al., J. Bacteriol. 152:000--000, 1982), we show that in response to Tris, NAPS accumulated to as much as 40% of the total cellular phospholipid content. NAPS accumulation began immediately upon addition of Tris and was reflected as an abrupt 12-fold increase in the apparent rate of NAPS accumulation. We suggest that Tris altered the flow of metabolites through a preexisting and previously unknown metabolic pathway. NAPS accumulation ceased immediately upon the removal of Tris; however, accumulated NAPS remained largely metabolically stable. Importantly, under conditions in which NAPS was not accumulated, the intracytoplasmic membrane was shown to be virtually devoid of newly synthesized NAPS. The significance of this observation is discussed in terms of its physiological implications on phospholipid transfer and membrane biogenesis in R. sphaeroides.